HIGH LEVEL OF INFORMATION CULTURE AS A MANDATORY FEATURE OF HIGH-SPIRITUAL PERSONALITY - N.V. Volkova (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the essence of informative culture of a person, the ways of it's rising in the context of informatization of society.